Sickle-cell disease in pregnant immigrants - Buckle, A. E. R. (1968)
Thirteen pregnancies in nine patients with sickle-cell disease, sickle-cell/haemoglobin C disease and sickle-cell/thalassaemia are reported. There was one maternal death and one stillbirth. Crises occurred in three of the four patients with sickle-cell disease but in only one of the three patients with sickle-cell/haemoglobin C disease.